2013
DOI: 10.1002/anzf.1017
|View full text |Cite
|
Sign up to set email alerts
|

Is Family Therapy Including Children?

Abstract: This paper presents a review of recent child therapy and family therapy texts and training courses in Australia. The aim was to determine the extent to which knowledge and information about child development and emotional and psychological problems in children and adolescents is included in the education and training of family therapists. The paper argues this is crucial to prevent the difficulties of young person's being ignored or exacerbated and discusses relevant ethical issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…There are many studies on engaging children in therapy and the importance of working systemically with the whole family (Higham et al, 2012;Oehlers & Shortland-Jones, 2013;O'Reilly, 2015;Raimondi & Walters, 2004;Rober, 2008;) although limited literature regarding working systemically with children in care (Barratt 2016;Peacock et al, 2016;Wilson, 2000).…”
Section: Findings From the Literaturementioning
confidence: 99%
“…There are many studies on engaging children in therapy and the importance of working systemically with the whole family (Higham et al, 2012;Oehlers & Shortland-Jones, 2013;O'Reilly, 2015;Raimondi & Walters, 2004;Rober, 2008;) although limited literature regarding working systemically with children in care (Barratt 2016;Peacock et al, 2016;Wilson, 2000).…”
Section: Findings From the Literaturementioning
confidence: 99%
“…Working with children requires knowledge of a child's developmental abilities and limitations in relation to their levels of communication (Oehlers, 2013) and a capacity to tune into the creative and playful world of the young child. Their polarised expressions of 'it's good' or 'bad', 'its my favourite' or 'I hate it', like ice-cream versus brussels sprouts, doesn't give voice to the full experience of a life lived in the many shades of colour.…”
Section: Engaging Children In Family Therapymentioning
confidence: 99%
“…Their polarised expressions of 'it's good' or 'bad', 'its my favourite' or 'I hate it', like ice-cream versus brussels sprouts, doesn't give voice to the full experience of a life lived in the many shades of colour. Working with children requires knowledge of a child's developmental abilities and limitations in relation to their levels of communication (Oehlers, 2013) and a capacity to tune into the creative and playful world of the young child. As Freeman, Epston, and Lobovits (1997) noted: 'Serious discussions and methodical problem solving may impose on children's communication, shutting out their voices, inhibiting their special abilities, knowledge and creative resources' (p. 3).…”
Section: Engaging Children In Family Therapymentioning
confidence: 99%
“…Highly relevant to this article is an investigation of content relating to children in family therapy texts and family therapy training programs in Australia. Oehlers and Shortland‐Jones (2013) found that of 10 family therapy textbooks published from 2010–2012, only three contained content specific to children, and of the 14 family therapy courses reviewed only three ‘contained units devoted solely to working with children’ (p. 221). Moreover, in the absence of such content within family therapy courses, it is possible to gain entry to the family therapy profession without having studied this in a previous qualification.…”
Section: Introductionmentioning
confidence: 99%